Tree resources Of Katerniaghat Wildlife Sanctuary, Uttar Pradesh, India with especial emphasis on conservation status, phenology and economic values - Lal Babu Chaudhary; Anoop Kumar; Ashish K Mishra; Nayan Sahu; Jitendra Pandey; Soumit K Behera; Omesh Bajpai (International Journal of Environment, 2014)
Uttar Pradesh, one of the most populated states of India along international border of Nepal, contributes only about 3% of total forest & tree cover of the country as the major parts of the area is covered by agriculture lands and human populations. The forests are quite fragmented and facing severe anthropogenic pressure in many parts. To protect the existing biodiversity, several forest covers have been declared as National Parks and Wildlife Sanctuaries. In the present study, Katerniaghat Wildlife Sanctuary (KWS) has been selected to assess tree diversity, their phenology and economic values as the trees are the major constituent of any forest and more fascinating among all plant groups. The sanctuary consists of tropical moist deciduous type of vegetation and situated along the Indo-Nepal boarder in Bahraich district of Uttar Pradesh, India. After, thorough assessment of the area, a list of 141 tree species belonging to 101 genera and 38 families have been prepared. The family Fabaceae exhibits highest generic and species diversity with 14 genera and 23 species. The genus Ficus of Moraceae has been found the largest with 11 species. Maximum trees with about 51 species have been found to flower in post winter season (February to March) in the forest. About 62 trees are used as medicinal for various purposes, 50 as ornamental & avenue trees, 37 as timber wood, 36 as edible, 16 as fire wood and 12 as fodder. Since the sanctuary area has been surrounded by several villages and facing anthropogenic pressure, the public awareness program related with biodiversity conservation and sustainable uses is highly needed to protect the forest covers. DOI: http://dx.doi.org/10.3126/ije.v3i1.9949 International Journal of Environment Vol.3(1) 2014: 122-133